2012
DOI: 10.1175/jcli-d-11-00631.1
|View full text |Cite
|
Sign up to set email alerts
|

Climatological Evolution of the Okinawa Baiu and Differences in Large-Scale Features during May and June

Abstract: The Okinawa baiu (summer rainy season) starts in early May and ends in late June, preceding the baiu in mainland Japan by approximately 1 month. This study investigates the time evolution of the large-scale circulation associated with the Okinawa baiu using 10-yr (1997-2006) climatologies of precipitation and meteorological fields, with particular focus on temperature advection at 500 hPa.The onset of the Okinawa baiu occurs in early May and is followed by an initial peak in precipitation during mid-May. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…In P_OB, precipitation peaks at approximately 12 mm day −1 in mid-June, and this peak is consistent with the GPCP_1DD. Precipitation in the GPCP_1DD shows a temporal peak in mid-May, before the peak in mid-June, which corresponds to the Okinawa Baiu (Okada and Yamazaki 2012). However, the AGCM does not reproduce this peak (Fig.…”
Section: Monthly Mean Precipitation and Future Changesmentioning
confidence: 98%
See 2 more Smart Citations
“…In P_OB, precipitation peaks at approximately 12 mm day −1 in mid-June, and this peak is consistent with the GPCP_1DD. Precipitation in the GPCP_1DD shows a temporal peak in mid-May, before the peak in mid-June, which corresponds to the Okinawa Baiu (Okada and Yamazaki 2012). However, the AGCM does not reproduce this peak (Fig.…”
Section: Monthly Mean Precipitation and Future Changesmentioning
confidence: 98%
“…With the progress of the Baiu season in East Asia, the zonal contrast of temperature in the mid-troposphere becomes enhanced; this is because the heated surface of the Asian continent, especially the Tibetan Plateau, and latent heating by monsoonal convection in South Asia, warm the troposphere aloft, leading to a larger difference in mid-troposphere temperature between the Tibetan Pla- teau and the Baiu frontal zone (Kato 1989;Kodama 1993;Ose 1998;Sampe and Xie 2010). The westerlies jet emanating from the eastern flank of the Tibetan Plateau transports the warmer air to the southern part of China and toward the Japanese islands (Sampe and Xie 2010;Okada and Yamazaki 2012). Therefore, warm-air advection is examined here.…”
Section: Future Changes In Atmospheric Conditions Due To the Differenmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that interannual variability of the EASM circulations is linked to the Tibetan Plateau thermal conditions and India Ocean sea surface temperature (SST) anomalies (Li and Yanai, ; Zhao et al , ; Liu and Wang, ; Hu and Duan, ). These processes are complicated by the varying mid‐tropospheric temperature advection within the Meiyu rainband (Kosaka et al , ; Okada and Yamazaki, ). However, few studies have focused on the interdecadal variability of Meiyu.…”
Section: Introductionmentioning
confidence: 99%
“…A global climate simulation conducted at a horizontal resolution that is too low to resolve topographic effects and small-scale processes encounters an inevitable drawback in reproducing the East Asian climate (Lau and Ploshay, 2009;Li et al, 2015). Regarding the East Asian quasi-stationary precipitation during spring-early summer (Ding and Chan, 2005;Chiang et al, 2015), that is, spring persistent rains (Tian and Yasunari, 1998;Wan and Wu, 2007;Linho et al, 2008) through pre-Meiyu and Okinawa Baiu to Meiyu-Baiu (Chen et al, 2004;Srivastava et al, 2004;Okada and Yamazaki, 2012;Wang et al, 2016), in addition to the effects of the massive Tibetan Plateau (Sampe and Xie, 2010;Chen and Bordoni, 2014), mesoscale high mountains have received increasing attention because of their substantial effects on the synoptic-to-large-scale monsoon dynamics (Shi et al, 2008;Qi and Wang, 2012;Wang and Chang, 2012;Wu et al, 2014;Wu and Hsu, 2016).…”
Section: Introductionmentioning
confidence: 99%